Rifampicin Induces Gene, Protein, and Activity of P-Glycoprotein (ABCB1) in Human Precision-Cut Intestinal Slices - Martinec, Ondrej; Biel, Carin; de Graaf, Inge A. M.; Huliciak, Martin; de Jong, Koert P.; Staud, Frantisek; Cecka, Filip; Olinga, Peter; Vokral, Ivan; Cerveny, Lukas (Frontiers in Pharmacology, 2021)
P-glycoprotein (ABCB1), an ATP-binding-cassette efflux transporter, limits intestinal absorption of its substrates and is a common site of drug-drug interactions. Drug-mediated induction of intestinal ABCB1 is a clinically relevant phenomenon associated with significantly decreased drug bioavailability. Currently, there are no well-established human models for evaluating its induction, so drug regulatory authorities provide no recommendations for in vitro/ex vivo testing drugs’ ABCB1-inducing activity. Human precision-cut intestinal slices (hPCIS) contain cells in their natural environment and express physiological levels of nuclear factors required for ABCB1 induction. We found that hPCIS incubated in Williams' Medium E for 48 hours maintained intact morphology, ATP content, and ABCB1 efflux activity. Here we asked whether rifampicin (a model ligand of pregnane X receptor, PXR), at 30 µM, induces functional expression of ABCB1 in hPCIS over 24- and 48-hour incubation (time to allow complete induction to occur). Rifampicin significantly increased gene expression, protein levels and efflux activity of ABCB1. Moreover, we described dynamic changes in ABCB1 transcript levels in hPCIS over 48 hours incubation. We also observed that peaks of induction are achieved among donors at different times and the extent of ABCB1 gene induction is proportional to PXR levels in the intestine. In conclusion, we showed that hPCIS incubated in conditions comparable to those used for inhibition studies can be used to evaluate drugs’ ABCB1-inducing potency in the human intestine. Thus, hPCIS may be valuable experimental tools that can be prospectively used in complex experimental evaluation of drug-drug interactions.